A new biosensor based on PVDF film for detection of nucleic acids. (July 2015) - Zhao, Bei; Hu, Jie; Ren, Wei; Xu, Feng; Wu, Xiaoqing; Shi, Peng; Ye, Zuo-Guang
Abstract: Nucleic acid testing (NAT) promises stable, safe, selective and specific detection of infectious and inherited diseases. However, conventional technologies, such as gel electrophoresis, ultraviolet spectrometry and fluorescent PCR, are labor-intensive and time-consuming, and require specialized instruments and professional staff. In this study, we developed a new diaphragm mass biosensor based on polyvinylidene fluoride (PVDF) piezoelectric film for detection of nucleic acids. A capture probe immobilized on the gold film of the biosensor via Au–S reaction has been designed. To improve the specificity of the biosensors, 6-mercapto-1-hexanol (MCH) as a blocking reagent after capture probe immobilization was employed. The nucleic acid hybridization between capture probe and target analyte was used in the experiment. The real mass load added on the diaphragm was proportional to the amount of target nucleic acids. The fluorescent measurement was used to validate the experiment and served as a control. The biosensor developed in the study can provide a cost-effective platform for NAT, thus holding potential for disease screening.